2005
DOI: 10.1681/asn.2004121100
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine as Marker of Kidney Function in South Asians

Abstract: Migrant populations of South Asian origin have a higher risk for chronic kidney disease than the native whites. Several formulas have been developed to estimate kidney function from serum creatinine concentration. However, none of these has been validated in the South Asian population, which generally has different muscle mass composition than whites. A population-based cross-sectional study was performed on 262 individuals who were aged >40 yr in Karachi, Pakistan. Reduced GFR was defined as creatinine cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 26 publications
6
84
0
1
Order By: Relevance
“…However, a study on general practitioners (GPs) in Karachi showed that 78% of them would rely on serum creatinine for detection of kidney disease [38]. Evidence has shown that eGFR measurement in Pakistan by the MDRD equation or calculating the creatinine clearance using the Cockcroft Gault equation is a better predictor of reduced GFR than serum creatinine alone [43], and using serum creatinine alone may result in significant under-recognition of CKD as the level may still be within normal range even when the kidney function is impaired significantly.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study on general practitioners (GPs) in Karachi showed that 78% of them would rely on serum creatinine for detection of kidney disease [38]. Evidence has shown that eGFR measurement in Pakistan by the MDRD equation or calculating the creatinine clearance using the Cockcroft Gault equation is a better predictor of reduced GFR than serum creatinine alone [43], and using serum creatinine alone may result in significant under-recognition of CKD as the level may still be within normal range even when the kidney function is impaired significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not have information on height or weight to calculate patient body surface area or ideal body weight. There are known reported limitations of the widely used MDRD equation, particularly for Asians (17), which are only partly explained by differences in body size. Because our information on this category is by definition quite limited, our conclusions must also be quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clearance measurements are still required for groups who were underrepresented in the original MDRD sample in order to fully validate the formula for all patients. These include: patients at extremes of age and body size; severely malnourished or obese patients; patients with skeletal muscle diseases, paraplegia, or quadriplegia, vegetarians, and those with rapidly changing kidney function as in acute kidney injury (19,22). The MDRD and C-G equations are inappropriate to estimate GFR in healthy individuals and have been shown to clearly underestimate GFR above approximately 60 mL·min -1 ·1.73 (m 2 ) -1 and to markedly overestimate GFR below approximately 20 mL·min -1 ·1.73 (m 2 ) -1 and in nephrotic range proteinuria (23)(24)(25).…”
Section: Equations Estimating Gfr Based On Creatininementioning
confidence: 99%